Protein glycation and methylglyoxal metabolism in Parkinson's disease - Vicente Miranda, Hugo (2009)
Tese de doutoramento, Bioquímica (Regulação Bioquímica), Universidade de Lisboa, Faculdade de Ciências, 2010